Investigation of wave-driven currents and statistical moments of irregular waves over a one dimensional horizontal fringing reef. (July 2021) - Fu, Ruili; Ma, Yuxiang; Dong, Guohai
Highlights: Wave-driven currents by irregular waves on a unidirectional fringing reef are investigated numerically. Wave-driven currents increase with increasing significant wave height and seaward depth. Variations of statistical moments for horizontal velocities are more significant with seaward depth deeper. The maximum kurtosis of velocities locates downstream on the flat compared with the wave surfaces. Abstract: Effects of significant wave height and seaward depth on the distribution of the wave-induced set-up, wave-driven currents and the statistical moments (kurtosis and skewness) of the horizontal velocities and surface elevations of irregular waves propagating over a fringing reef are investigated using a fully non-hydrostatic wave model. It is found that wave-induced set-up and wave-driven currents obviously increase with increasing significant wave height and seaward depth. Besides, as the seaward depth is relatively shallow, the local maximum skewness of horizontal fluid velocities and surface elevations are achieved nearly at the same location. However, the location of the maximum kurtosis of the horizontal fluid velocities is on the inshore side of the flat compared to that of the surface elevations. Additionally, as a seaward depth increases, variations of skewness and kurtosis of horizontal velocities are more significant compared to surface elevations, and the maximum kurtosis and skewness of the horizontal velocities located downstream compared to those of the surface elevations.